A qualitative evaluation of the pathway for eating disorders and autism developed from clinical experience (PEACE): clinicians’ perspective - Li, Zhuo; Hutchings-Hay, Chloe; Byford, Sarah; Tchanturia, Kate (Frontiers in Psychiatry, 2024)
The Pathway for Eating disorders and Autism developed from Clinical Experience (PEACE pathway) is a clinical pathway of adapted treatment for individuals with eating disorders and autism in the UK. This study aims to investigate multidisciplinary clinicians' views of the strengths and challenges of PEACE pathway adaptations, while identifying areas where further improvement is needed.Method: Semi-structured interviews were conducted with 16 clinicians who worked on the PEACE pathway. Themes relevant to the benefits, challenges and areas of improvement were identified, and a thematic map was produced.Results: PEACE Pathway brought clinical benefits such as improved understanding of patients' perspective, improved flexibility and individualisation in clinicians' approach, increased patient engagement, and provision of resources that are helpful to all patients with or without autism. Benefits to the service included increase in autism awareness, clinicians' confidence, and team collaboration. Challenges were also identified, including difficulties in incorporating autism adaptations into existing treatment protocol, implementing PEACE at different levels of care, staff schedule conflicts, and increased pressure to meet patients' needs. Overall, there is a need for systemic improvement in aftercare and community support for autism, more suitable autism screening tool, and more structured guidelines for making adaptations.